The Influence Of Workload, Physical Work Environment, And Job Burnout On The Performance Of Public High School Teachers In Palembang City - Naurah Nazhifah; Zunaidah, Zunaidah; Yos Karimudin; M. Ichsan Hadjri; Wita Farla WK (Jurnal Ekonomi, 2024)
This study aims to empirically prove and analyze various factors affecting the performance of public high school teachers in Palembang. It investigates the impact of workload, the influence of the physical work environment, and the effects of job burnout on teacher performance. Additionally, the study assesses the combined effect of these factors on teacher performance. By doing so, the research seeks to provide a comprehensive understanding of how workload, physical work environment, and job burnout contribute to the performance of public high school teachers in Palembang.The research employed a quantitative approach, utilizing numerical data and measurements. Conducted at public high schools in Palembang, the study focused on public high school teachers (PNS) as its subjects. It aimed to examine the impact of workload, physical work environment, and burnout on teacher performance. The population consisted of public high school teachers in Palembang, with a sample of 279 teachers selected through proportional random sampling. Data collection was carried out using closed questionnaires directly filled out by the teachers; the workload, physical work environment, and burnout questionnaires were completed by the teachers, while the performance questionnaires were filled out by the vice principals. These questionnaires were based on theoretical foundations and relevant dimensions, tailored to meet the research objectives. Data analysis was performed using SPSS software, release 22. Based on the analysis, several conclusions have been drawn. Firstly, workload has a positive but not significant impact on teacher performance. Secondly, the physical work environment has a positive and significant influence on teacher performance. Thirdly, job burnout negatively and significantly affects teacher performance. Lastly, workload, physical work environment, and job burnout collectively have a simultaneous and significant effect on teacher performance. These findings highlight the importance of managing workload and enhancing the physical work environment to improve teacher performance while addressing job burnout to prevent its negative impact.